Kadar Kolesterol Total Tikus Hiperkolesterolemia dengan Pemberian Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomoea batatas (L.) Lam) - Siti Fatimah; Desto Arisandi; Meirina Sindi Saputri (Journal of Health (JoH), 2018)
The increase in total cholesterol level increases the risk of cardiovascular disease. Sweet potato leaves are a food that contains polyphenols, flavonoids, quercetin, tannin, and fiber that effectively lower total cholesterol levels. This study aims to analyze the effect of ethanol extracts of leaf purple sweet potato on serum total cholesterol levels of rats fed a high-fat diet. An experimental study with design pre and posttest carried out on 10 male Wistar rats (Rattus norvegicus) fed a high-fat, which are 2 groups: 1 group the control hypercholesterolemia and 1 group ethanol extracts of leaf purple sweet potato. Dose based on leaves of quercetin that is equal to 2 mg/kgBB. The average content of quercetin ethanol extracts of leaf purple sweet potato was analyzed to obtain 14,08 mg/100g. Ethanol extracts of leaf purple sweet potato are given for 14 days by way of on the sonde. Serum total cholesterol was determined by the CHOD-PAP method. The data obtained were analyzed descriptively.The result of this study obtained the average total cholesterol level of white blood rats before giving ethanol extracts of leaf purple sweet potato that is 189,89 mg/dl, whereas after administration of ethanol extracts of leaf purple sweet potato dose 2 mg/kgBB that is 131,92 mg/dl. The decrease in total cholesterol level of white rats after giving ethanol extracts of leaf purple sweet potato with dose 2 mg/kgBB that is 30,52 %.